Melancholicy nad Wisłą - Piechota, Dariusz (Wydawnictwo Uniwersytetu Rzeszowskiego, 2018)
The theme of melancholy in the Polish prose of the 21st century is still valid and directly related to the issue of identity and maturity of protagonists. People who suffer from depression exist in a world in which “ all that is solid, melts into the air”. This feeling complicates their existence because they often cannot describe their own identity (both individual and collective). The modern homo melancholicus often treats his or her own life as someone else’s project, which intensifies the experience of incoherent self-image and sense of alienation. In the latest realistic prose, reflections on passing away appear in thirty-year-old protagonists who lose the illusion of a quick career which would give them (apparently) happiness. Recalling the past, rooted in communist Poland, turns out to be a type of autotherapy. Melancholics see their lives as scattered, deformed, similar to the puzzles that should be put together again. The ongoing depersonalization and identity problems make that the heroes wander around the labyrinth, looking for a way out of it. The experience of melancholy proves to be the experience of transgression in which a person can find himself by accepting the complexity of the world.
Melancholics on the Vistula River
Keywords: melancholy; youth; consumption; passing; depression; melancholia; młodość; konsumpcja; przemijanie; depresja